Pengembangan Bahan Ajar Digital-Interaktif Analisis Real Berbasis Moderasi Beragama untuk Mahasiswa PTKIN di Indonesia - Abdussakir, Abdussakir; Mukmin, Muhammad Islahul; Masamah, Ulfa (Institut Agama Islam Negeri Curup, 2024)
Instilling an attitude of religious moderation in State Islamic Religious Colleges (PTKIN) can be done using teaching materials based on religious moderation. Unfortunately, there are still few teaching materials that can be used for this purpose. This study aims to produce valid and practical digital-interactive teaching materials for Real Analysis based on religious moderation for PTKIN students in Indonesia. This development research combines the ADDIE model with the 4D model. Several experts were involved as validators and while fifth-semester students in the Mathematics Education Study Program were involved in the trial of the research product. Based on the validation results of material and language experts, teaching materials, and learning technology experts, mathematics learning design experts, and religious moderation experts, it was found that the teaching materials produced were very valid (3.39%). Based on small group trials, large groups, and lecturer responses, it was found that the teaching materials produced were very practical (83.22%). Thus, the digital-interactive teaching materials for Real Analysis based on religious moderation are very suitable for use by PTKIN students in Indonesia.